Digital Organization Affecting the Effectiveness of Educational Administration in the Office of the Primary Educational Service Area Phetchaburi Area 2 - thaworn, nuttavut (Education journal Faculty of Education, Nakhon Sawan Rajabhat University, 2025)
This research aims to 1) study the level of digital organization of educational institutions, 2) study the level of effectiveness of educational administration, and 3) analyze the effect of digital organization on effectiveness of educational administration in the Office of the Primary Educational Service Area, Phetchaburi Area 2. This is a quantitative research. The sample group is administrators and teachers under the jurisdiction of Phetchaburi Primary Educational Service Area Office 2, totaling 316 people. The sample group was determined using Taro Yamane’s table. A multi-stage sampling method was used. The research tool was a 5-level rating scale questionnaire. The statistics used to analyze the data included percentage, mean, standard deviation, and stepwise multiple regression analysis. The research results found that. Digital organization has an average value at a high level, ranked from highest to lowest as follows: personnel competence, organizational culture, technology, and work structure and process. 2) Effectiveness of educational institution administration has an average value at a high level, ranked from highest to lowest as follows: academic achievement, problem solving within the school, school change and development, and positive attitude. And 3) Digital organization that affects the effectiveness of educational institution administration is organizational culture, technology, personnel competence, and work structure and process.